Differential epigenetic regulation of glucose-induced alteration of miR-9 in retinal and cardiac endothelial cells - Eric Wang; Biao Feng; Shali Chen; Subrata Chakrabarti (PLoS ONE, 2026)
Diabetic complications are significant causes of reduced quality of life among people living with diabetes. Endothelial dysfunction is a core component of diabetic complications. Microvascular endothelial cells from the heart and retina, two major targets of microvascular complications of diabetes, respond largely uniquely to diabetic insult. However, both involve inhibition of microRNA 9 (miR-9), a microRNA that when upregulated, helps maintain e&ndothelial function and characteristics. We have found that miR-9 is regulated by the long non-coding RNA ZFAS1 through targeted histone methylation in the heart. But given the disparate responses of retinal and cardiac endothelial cells to hyperglycemia, we wanted to investigate the upstream regulation of glucose-induced miR-9 inhibition in retinal endothelial cells. To this effect, we used human retinal and cardiac microvascular endothelial cells, treated with histone methylation inhibitors, DNA methylation inhibitors, or transfected with various siRNAs. We found that despite miR-9 being similarly affected by high glucose in retinal and cardiac endothelial cells, miR-9 is regulated through different epigenetic mechanisms in retinal and cardiac endothelial cells. Whereas cardiac endothelial cells relied on targeted histone methylation through ZFAS1, we showed that retinal endothelial cells relied more on DNA methylation, influenced by both ZFAS1 and the long non-coding RNA MALAT1, with ZFAS1 and MALAT1 influencing the expressions of one another. Our findings highlight the differences between regulatory mechanisms of similar processes across similar cell types, but point to miR-9 inhibition as a point of convergence between cardiac and retinal endothelial dysfunction may open the door for multi-organ targeted therapeutics.